2011
DOI: 10.1002/pbc.23311
|View full text |Cite
|
Sign up to set email alerts
|

Excessive daytime sleepiness and sleep‐disordered breathing disturbances in survivors of childhood central nervous system tumors

Abstract: Background Improvements in treatment and management for pediatric central nervous system (CNS) tumors have increased survival rates, allowing clinicians to focus on long-term sequelae, including sleep disorders. The objective of this study was to describe a series of CNS tumor survivors who had sleep evaluations that included polysomnography with attention to sleep disorder in relation to the tumor site. Procedure We report on 31 patients who had retrievable reports including an overnight polysomnography (PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 34 publications
(36 reference statements)
1
75
1
Order By: Relevance
“…This is in contrast to previous studies that have found higher rates of sleep complaints in survivors of centrally located brain tumors [4,8,13]. Of note, these previous studies have focused on children referred to sleep disorders centers, which may reflect a referral bias whereby providers are anticipating sleep disturbance in children with tumors of the central brain region and may be less likely to query the daytime sleepiness of children with hemispheric or infratentorial tumors.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…This is in contrast to previous studies that have found higher rates of sleep complaints in survivors of centrally located brain tumors [4,8,13]. Of note, these previous studies have focused on children referred to sleep disorders centers, which may reflect a referral bias whereby providers are anticipating sleep disturbance in children with tumors of the central brain region and may be less likely to query the daytime sleepiness of children with hemispheric or infratentorial tumors.…”
Section: Discussioncontrasting
confidence: 75%
“…Accordingly, endocrinopathies, sensory and motor deficits, pain, cognitive decline, heart failure, stroke, and epilepsy are among the commonly reported late effects of treatment in brain tumor survivors [1,2,7]. In addition, child survivors have rated the long-term treatment effects of fatigue and sleepiness as their most distressing symptom, and symptoms may go unrecognized until years after diagnosis [8]. The disrupted sleep patterns, significant fatigue, and excessive daytime sleepiness (EDS) experienced during and after treatment are potentially remediable conditions that contribute to substantial morbidity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indirect sleep disorders also occur as a consequence of brain tumours in children when the tumour results in injury to either the respiratory control centre of the medulla leading to central sleep apnoea, or to the glossopharyngeal, vagus and hypoglossal nerves innervating the pharyngeal dilator muscles, leading to obstructive sleep apnoea [15,59]. Both central and obstructive sleep apnoea cause sleep disruption and fragmentation [60,61].…”
Section: Sleep In Children With Cancer Of the Brain And Central Nervomentioning
confidence: 98%
“…Children with neoplasms of the CNS also commonly had more than one sleep problem, usually both EDS and SDB. A further study of 31 CNS tumour survivors who were referred for assessment of sleep disorders, on average 6.9 y following tumour diagnosis (mean age at diagnosis was 7.4 y), identified that EDS remained the most common reason for referral [59]. Of the sleep disorders diagnosed, obstructive sleep apnoea was the most common (14 children), followed by central sleep apnoea (four children), hypersomnia (four children) and narcolepsy (three children).…”
Section: Sleep In Children With Cancer Of the Brain And Central Nervomentioning
confidence: 99%